Pentane and other volatile organic compounds, including carboxylic acids, in the exhaled breath of patients with Crohn's disease and ulcerative colitis - Dryahina, Kseniya; Smith, David; Bortlík, Martin; Machková, Naděžda; Lukáš, Milan; Španěl, Patrik (Journal of breath research, 2017)
A study has been carried out on the volatile organic compounds (VOCs) in the exhaled breath of patients suffering from inflammatory bowel disease (IBD), comprising 136 with Crohn's disease (CD) and 51 with ulcerative colitis (UC), together with a cohort of 14 healthy persons as controls. Breath samples were collected by requesting the patients to inflate Nalophan bags, which were then quantitatively analysed using selected ion flow tube mass spectrometry (SIFT-MS). Initially, the focus was on n-pentane that had previously been quantified in single exhalations on-line to SIFT-MS for smaller cohorts of IBD patients. It was seen that the median concentration of pentane was elevated in the bag breath samples of the IBD patients compared to those of the healthy controls, in accordance with the previous study. However, the absolute median pentane concentrations in the bag samples were about a factor of two lower than those in the directly analysed single exhalations-a good illustration of the dilution of VOCs in the samples of breath collected into bags. Accounting for this dilution effect, the concentrations of the common breath VOCs, ethanol, propanol, acetone and isoprene, were largely as expected for healthy controls. The concentrations of the much less frequently measured hydrogen sulphide, acetic acid, propanoic acid and butanoic acid were seen to be more widely spread in the exhaled breath of the IBD patients compared to those for the healthy controls. The relative concentrations of pentane and these other VOCs weakly correlate with simple clinical activity indices. It is speculated that, potentially, hydrogen sulphide and these carboxylic acids could be exhaled breath biomarkers of intestinal bacterial overgrowth, which could assist therapeutic intervention and thus alleviate the symptoms of IBD.
Keywords: ulcerózní kolitida; Young Adult; Crohn Disease; butadieny; Male; biologické markery; Butadienes; dechové testy; mladý dospělý; Biomarkers; Adolescent; Hemiterpenes; pentany; kyseliny karboxylové; Crohnova nemoc; Adult; Acetic Acid; Aged; dospělí; mužské pohlaví; senioři; sulfan; hemiterpeny; Steam; Breath Tests; mladiství; Hydrogen Sulfide; kyselina octová; lidé; ženské pohlaví; těkavé organické sloučeniny; vydechnutí; Humans; Volatile Organic Compounds; Colitis, Ulcerative; Carboxylic Acids; pára; Female; lidé středního věku; Exhalation; Pentanes; Middle Aged